News agency coverage of conflict among Russia’s political elite - Frampton, Anthony and Boyd-Barrett, Joseph Oliver (2012)
"This study reviews coverage of a spat between Moscow Mayor Yury Luzhkov and Russian President Dmitry Medvedev in 2009 and 2010, analyzing how the Thomson Reuters and Interfax news agencies report on conflict among political elites in post-Soviet and post-perestroika Russia. Using framing theories and discourse and thematic analyses, the research deconstructs the reports from the two agencies, one headquartered in London and New York and the other in Moscow, analyzing how they comply with Western journalistic principles while navigating the constraints on professional journalism in Russia. The qualitative study concludes that orientation, reporting conventions, and editorial decisions led Interfax and Reuters to privilege certain perspectives while downplaying others." [Information des Anbieters]
https://katalog.adlr.link/Record/finc-80-20964